An assessment of health-related quality of life using generic and HIV-specific instruments among patients receiving antiretroviral therapy at a general hospital in central Thailand - Pongmesa, Tipaporn; Luckanajantachote, Pranee; Kositchaiwat, Kulvaree; Waewpunyasin, Jantapa; Trongtrakarn, Panida; Oransuwanchai, Arunroj (Science, Engineering and Health Studies, 2018)
This cross-sectional study aimed to assess the health-related quality of life (HRQoL) among 210 HIV-positive patients receiving antiretroviral therapy (ART) at a general hospital in Central Thailand, and to analyze correlations between scores from HIV-specific and generic HRQoL instruments. A small majority of the participants were female (56.2%) with a mean (SD) age of 43.3 (7.9) years. An assessment using the World Health Organization Quality of Life-HIV Brief Version (WHOQOL-HIV BREF) demonstrated that most participants reported moderate levels for overall HRQoL (71.9%) and general health (40.5%). The mean scores of the six domains ranged from 12.64 to 16.20 out of a total score of 20, with the lowest and highest scores being reported for ‘social relationships’ and ‘spiritual/personal beliefs/religion’. For the 5-level EuroQol-5 dimension (EQ-5D-5L), most participants reported ‘no problems’ in any of the five health dimensions, with mean (SD) EQ-5D-5L utility and EQ VAS scores of 0.93 (0.08) and 81.43 (15.75) respectively. All the general items and domain scores of the WHOQOL-HIV BREF significantly correlated with both the EQ-5D-5L utility and EQ VAS scores (p < 0.05), but the correlations were considered either weak or moderate. Our results provided a better understanding of the HRQoL of these patients and suggested certain important aspects concerning the patients’ HRQoL that should be integrated into patient counseling and education.